PENGARUH KUALITAS PELAYANAN DAN CITRA DESTINASI PADA NIAT KUNJUNGAN ULANG: KEPUASAN WISATAWAN DAN PENGALAMAN BERKESAN SEBAGAI VARIABEL INTERVENING - Muhammad Naim; Primasatria Edastama (POLITEKNIK LP3I JAKARTA, 2026)
Memorable experiences play a crucial role in fostering tourist loyalty. This study aims to analyze the influence of service quality and destination image on satisfaction, memorable experiences, and revisit intention at The Nice Park. A quantitative method with Structural Equation Modeling (SEM) using SPSS 25 and SmartPLS 3.0 was applied. Data were collected from 120 respondents through purposive sampling. The findings reveal that most relationships are significant, particularly the effects of service quality and destination image on memorable experiences and revisit intention. However, the direct effects of service quality on satisfaction, destination image on revisit intention, and satisfaction on revisit intention were not significant, highlighting the mediating role of memorable experiences. This study is limited by variations in branch management and external factors such as weather and seasonal visits. Future research is suggested to include multiple branches for comparative analysis, refine the measurement of memorable experiences, and integrate word-of-mouth variables. Managerial implications emphasize the importance of creating emotional and personalized experiences, maintaining consistent branding, collaborating with local government and content creators, and offering group packages to expand the market.